Z dyskusji parlamentarnej nad powołaniem Komisji Wojskowej w początkach obrad Sejmu Wielkiego - Szczygielski, Wojciech (Przegląd Nauk Historycznych, 2009)
In October and at the beginning of November 1788 in the Sejm there was a debate on the abolition of the Military Department of the Permanent Council (dependent on Russia) and the establishment of the Military Commission. During the debate two visions of the Military Commission emerged. The dominating one was the concept promoted by the Puławy party and the independence-oriented deputies. According to this concept the Military Commission was an institution connected with the reformist roots of "The Family" from 1764. This vision of the Military Commission appealed to the gentry because it realised the concept of the democratic (civic) state referring to the emancipation and anti-magnate tendencies of the provincial gentry. The other concept of the Military Commission was formulated by the royal party in order to keep the Permanent Council and the Military Department. It was a vision of the Military Commission which was temporarily (in the years 1775-1776) dominated by hetman Franciszek Ksawery Branicki and which, as a result, was treated as an institution allegedly susceptible to hetman's influence. Finally, the concept of the Military Commission promoted by the Puławy party and the independence-oriented deputies won. The parliamentary debate ending in the abolition of the Military Department and the establishment of the Military Commission (during the session of 3rd November 1788) shows how close the Enlightenment breakthrough initiated by "The Family" in 1764 was to the landed gentry (prevailing in the Sejm).